2021
DOI: 10.1007/s10725-021-00755-z
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming of plants aiding in drought stress tolerance and faster recovery: a review

Abstract: Drought stress exposure adversely affects plant growth and productivity. Various seed priming techniques are experimented to mitigate the adverse effect of drought stress on plant performance. It is a low-cost and sustainable technology that proved to be of immense potential to enhance drought tolerance and increase crop productivity. Drought episodes are followed by recovery through rain or irrigation and help the plants to recuperate from the damages caused by drought stress. The severity of drought-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…This could be because of the development of defense mechanisms in the SH-8-treated seeds, including increased antioxidant production and changes in osmotic processes. This mechanism originates from the primary memory, which can be established after secondary exposure, and is known as prime-omics ( Khomari et al., 2018 ; Srivastava et al., 2021 ) ( Aswathi et al., 2021 ). The germination percentage decreased linearly with an increase in the concentration of PEG.…”
Section: Resultsmentioning
confidence: 99%
“…This could be because of the development of defense mechanisms in the SH-8-treated seeds, including increased antioxidant production and changes in osmotic processes. This mechanism originates from the primary memory, which can be established after secondary exposure, and is known as prime-omics ( Khomari et al., 2018 ; Srivastava et al., 2021 ) ( Aswathi et al., 2021 ). The germination percentage decreased linearly with an increase in the concentration of PEG.…”
Section: Resultsmentioning
confidence: 99%
“…Priming, due to an inherently relatively high stability of photosystems and their high recovery response, offers a role in reducing the severity of stress and can therefore promote a rapid and complete recovery of plant physiological functions. Although different priming methods undoubtedly improve photosynthetic parameters and overall photosynthetic efficiency of plants exposed to various environmental stresses ( Vincent et al., 2020 ; Sorrentino et al., 2021 ; Aswathi et al., 2022 ; Johnson and Puthur, 2022 ), the control mechanisms that govern the photosynthetic protection are still poorly understood. Recently, a major role in both the direct and indirect regulation of the photosynthetic protection under stress conditions has been attributed to various plant hormones ( Müller and Munné-Bosch, 2021 ), which have long been known as effective priming agents ( Kauss and Jeblick, 1995 ; Mur et al., 1996 ; Ton and Mauch-Mani, 2004 ; Hirao et al., 2012 ; Wang et al., 2014 ; Ji et al., 2021 ).…”
Section: Mechanisms Of Cytokinin-mediated Effects On Photosynthesismentioning
confidence: 99%
“…70,71 DNA repair is a crucial event in seeds undergoing a sudden change from dormant to active phase, which induces DNA breakdown, ROS accumulation and obstructed cell division, and maintains seed viability, vigor and germination. 58,72,73 A transcriptome study revealed the differential expression of genes belonging to different functional categories, such as the defence response, metabolism of DNA/RNA, proteins, energy, cell wall, stress, and secondary metabolism in rice (Oryza sativa L.) plants primed with P. fluorescens and infected with Cnaphalocrocis medinalis. 74 Priming regulates the protein subunits (⊍ and ⊎ tubulin) for the maintenance of cell division, cellular cytoskeleton, cell growth and development.…”
Section: Induction Of Molecular Changes In Plantsmentioning
confidence: 99%